Sub-Tenon's local anaesthesia for the treatment of retinopathy of prematurity with diode laser. - Parulekar, M; Chen, S; Patel, C (2008)
PURPOSE: To evaluate the safety and efficacy of sub-Tenon's local anaesthesia (LA) for laser treatment of threshold retinopathy of prematurity (ROP). METHODS: A cohort of 18 eyes of 10 neonates with threshold ROP was treated with diode laser peripheral retinal ablation over 14 treatment sessions using oral sedation and sub-Tenon's anaesthesia. Treatment was performed in a neonatal unit. The heart and respiratory rate, trans-cutaneous oxygen saturation, and physical activity were continuously monitored for signs of neonatal distress. Cardio-respiratory stability during and after the procedure was scored for each eye treated using a Cardio-respiratory index described previously. RESULTS: In all cases, the planned dose of laser was delivered. One out of 18 eyes developed stage 4b tractional retinal detachment over a follow-up of at least 6 months for all babies. Systemic complications during treatment included transient bradycardia and apnoea requiring stimulation in two babies and excessive head mobility in three babies. Treatment duration varied between 20 and 80 min. Ocular complications were conjunctival haemorrhage and chemosis. The mean cardio-respiratory index was 1.13, which compared favourably with the standard published. CONCLUSIONS: Sub-Tenon's LA with oral sedation appears to be a safe and effective alternative to general anaesthesia for laser treatment of ROP, with the potential for lower morbidity.